2015
DOI: 10.1098/rspb.2015.1887
|View full text |Cite
|
Sign up to set email alerts
|

Annual coral bleaching and the long-term recovery capacity of coral

Abstract: Mass bleaching events are predicted to occur annually later this century. Nevertheless, it remains unknown whether corals will be able to recover between annual bleaching events. Using a combined tank and field experiment, we simulated annual bleaching by exposing three Caribbean coral species (Porites divaricata, Porites astreoides and Orbicella faveolata) to elevated temperatures for 2.5 weeks in 2 consecutive years. The impact of annual bleaching stress on chlorophyll a, energy reserves, calcification, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
116
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 47 publications
14
116
2
Order By: Relevance
“…P. damicornis and S. pistillata maintained their total energy reserves and biomass while F. favus lost total energy reserves and biomass. Interestingly, total energy reserves in all three species of Eilat corals, irrespective of bleaching status, were higher than levels found in corals that were the most susceptible to repeat bleaching in the Caribbean and consistent with findings that high energy reserves is a common trait found among the most thermally tolerant corals (Rodrigues and Grottoli, 2007;Anthony et al, 2009;Grottoli et al, 2014;Schoepf et al, 2015). While, we found no isotopic evidence of increases in heterotrophy as a mechanism for coping with the declines in photoautotrophically fixed carbon supply in bleached corals, the isotopic signature of F. favus suggests that it has a high baseline input of heterotrophic C, which could underlie its low mortality rate following bleaching events (McClanahan, 2004;Sutthacheep et al, 2013), despite its energy reserve and biomass losses.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…P. damicornis and S. pistillata maintained their total energy reserves and biomass while F. favus lost total energy reserves and biomass. Interestingly, total energy reserves in all three species of Eilat corals, irrespective of bleaching status, were higher than levels found in corals that were the most susceptible to repeat bleaching in the Caribbean and consistent with findings that high energy reserves is a common trait found among the most thermally tolerant corals (Rodrigues and Grottoli, 2007;Anthony et al, 2009;Grottoli et al, 2014;Schoepf et al, 2015). While, we found no isotopic evidence of increases in heterotrophy as a mechanism for coping with the declines in photoautotrophically fixed carbon supply in bleached corals, the isotopic signature of F. favus suggests that it has a high baseline input of heterotrophic C, which could underlie its low mortality rate following bleaching events (McClanahan, 2004;Sutthacheep et al, 2013), despite its energy reserve and biomass losses.…”
Section: Discussionsupporting
confidence: 71%
“…The host tissue isotope values were reported as δ 13 C h while the algal endosymbiont isotope data were reported as δ 13 C e . In general, as the incorporation of isotopically depleted zooplankton and other heterotrophic carbon sources (i.e., dissolved and particulate organic carbon) into coral tissues increases, the δ 13 C h decreases Levas et al, 2013;Schoepf et al, 2015). As the rate of photosynthesis increases, isotopic fractionation decreases, and endosymbiotic algae incorporate relatively less 12 C than 13 C into their tissues, resulting in increased δ 13 C e (Muscatine et al, 1989;Rodrigues and Grottoli, 2006).…”
Section: Stable Isotopic Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference between barrier and reef interior was driven in large part by the high calcification rates of corals on the western (leeward) barrier reef (1.39 ± 0.39 g·cm −2 ·yr −1 ), which were significantly greater than those on the eastern (windward) barrier (1.15 ± 0.43 g·cm −2 ·yr −1 ; p = 0.019) (see Appendix E). aspect that requires evaluation is the possibility of reduced thermal tolerance during the lifetime of a single colony, for which there is some evidence from experimental data (Schoepf et al, 2015). We do not find strong evidence for this in our coral cores, as we found that accreting a stress band during the 1998 bleaching event did not change the odds that an individual coral would form a stress band during the 2010 event.…”
Section: Resultscontrasting
confidence: 49%
“…Qualitative metrics at different time scales, such as the timing, fluctuations, and intensity of disturbances, will influence responses (McClanahan & Maina 2003, Ainsworth et al 2016. For acute stress, depending on length, bimodal qualities of the pre-stress disturbances, and whether or not corals have saved or depleted their energy reserves, coral taxa can be either more or less resistant to within-season thermal anomalies (Grottoli et al 2014, Schoepf et al 2015b.…”
Section: Introductionmentioning
confidence: 99%